2006
DOI: 10.1029/2005gc001233
|View full text |Cite
|
Sign up to set email alerts
|

Strontium to calcium ratios in the marine gastropod Conus ermineus: Growth rate effects and temperature calibration

Abstract: [1] Here we investigate the potential of Sr/Ca ratios in the marine gastropod Conus ermineus for reconstructing seawater temperatures. We present annually resolved records of Sr/Ca and d18 O for four shells collected alive from the Flower Garden Banks National Marine Sanctuary in the Gulf of Mexico. Our results show that variations in Sr/Ca and d18 O covary with the in situ seasonal temperature cycle. Sr/ Ca and temperature are positively correlated, in contrast with the inverse relationship found in inorganic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 43 publications
3
46
0
Order By: Relevance
“…These results are consistent with previous shell source analyses and work (e.g., Chave, 1954, Lerman, 1965Sosdian et al, 2006) that have suggested a positive relationship between the incorporation of strontium into shells and the water temperature of the growing environment among some gastropod mollusk species. On average, mean annual surface temperatures in the Gulf of Mexico are warmer than those along the Atlantic coast.…”
Section: Control Samplesupporting
confidence: 93%
“…These results are consistent with previous shell source analyses and work (e.g., Chave, 1954, Lerman, 1965Sosdian et al, 2006) that have suggested a positive relationship between the incorporation of strontium into shells and the water temperature of the growing environment among some gastropod mollusk species. On average, mean annual surface temperatures in the Gulf of Mexico are warmer than those along the Atlantic coast.…”
Section: Control Samplesupporting
confidence: 93%
“… Data sources: K01, Kobashi et al [2001]; S06, Sosdian et al [2006]; G08, Gentry et al [2008]; T10, Tao and Grossman [2010]; T12, Tao [2012]; S13, this paper; T13, Tao et al (submitted manuscript, 2012); GUD, E. L. Grossman (unpublished data, 2002); TUD, K. Tao (unpublished data, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that mollusc shell Sr/Ca is controlled by ambient solution and could provide a record of Sr/Ca sw [ Buchardt and Fritz , 1978; Lorens and Bender , 1980]. Temperature and growth rate also modify Sr/Ca in modern and fossil marine gastropods [ Purton et al , 1999; Sosdian et al , 2006; Gentry et al , 2008; Tripati et al , 2009]. These relationships have been used in a study of turritellid gastropods to suggest that between 64 and 37 Ma, Sr/Ca sw was higher than today [ Tripati et al , 2009], in contrast with results based on other biogenic and abiogenic proxies [ Lear et al , 2003; Coggon et al , 2010; Balter et al , 2011].…”
Section: Introductionmentioning
confidence: 99%
“…During faster crystal growth rates, near-surface migration of ions, which expel impurities, are less efficient and an increase in strontium replacement of calcium ions might be expected [38]. Strontium has also been found to be correlated with temperature indirectly by increased growth rates in marine gastropods [39]. The increased ratios of strontium in the shells of L. miliaris are therefore likely to be linked to the increased growth rates observed, although other abiotic influences may also affect this relationship.…”
Section: Discussionmentioning
confidence: 99%